DERBENT IN THE STRUCTURE OF THE RUSSIAN EASTERN TRADE AT THE TURN OF THE XVII - FIRST QUARTER OF THE XVIII CENTURY - Magomedov, N A (History, Archeology and Ethnography of the Caucasus, 2015)
Basing on the analysis of archival documents and literarysources the author studies the role of Derbent as a transit node in the implementation of Russia’s eastern trade that accepted new rates of development during the reign of Peter I. The article presents geographical, socio-economicand political factors that contributed to make Derbentone of the centers of international trade in the western part of the Caspian Sea region. The author provides figures of trade transactions of Indian, Armenian, Russian and Derbent merchants, shows the range of goods transited through Derbent from Russia to the East and back. The study shows that eastern merchants, specializing in re-export of eastern goods to Russian towns and export of Russian goods to the eastern countries, playeda significant role in involvement of Derbent in international and especially Russian-eastern trade.